Pedagogical support and the teaching role in full school day: Case of educational institutions Santa Rosa and Salesianos of San Juan Bosco - Puno Peru - Yana Salluca, Marisol (2018)
This study focused on the strategy of pedagogical support and the new role of the teacher in the pilot secondary educational institutions with full school day, Santa Rosa and Salesians of San Juan Bosco of the city of Puno Peru, during the academic year 2015. The research was non-experimental, transectional, descriptive and correlational. Data were collected using a closed survey of opinion poll of 92 protagonist teachers chosen at random. The results indicate that the level of teaching performance in the process of planning, development and evaluation, in domain I and domain II are between the good category (10%) very good (85%) and excellent (5%) with a Pearson's r coefficient = 0.763 **, so it is concluded that there is a high and direct positive correlation between the pedagogical support for the teacher and the new role of teachers as the main factor of educational success in secondary educational institutions with a full school day in the city of Puno.